Can pneumococcal meningitis surveillance be used to assess the impact of pneumococcal conjugate vaccine on total invasive pneumococcal disease? A case-study from South Africa, 2005–2016. Issue 38 (10th September 2019) - Kleynhans, Jackie; Cohen, Cheryl; McMorrow, Meredith; Tempia, Stefano; Crowther-Gibson, Penny; Quan, Vanessa; de Gouveia, Linda; von Gottberg, Anne; ,
Abstract: Introduction: South Africa introduced seven-valent pneumococcal conjugate vaccine (PCV7) in 2009 and PCV13 in 2011. We aimed to compare the estimated impact of PCV on pneumococcal meningitis (PM) to impact of PCV on total invasive pneumococcal disease (tIPD) based on risk reduction after PCV introduction. Methods: We conducted national, laboratory-based surveillance for tIPD during 2005–2016. We estimated and compared rates of PCV13 and non-PCV13 serotype disease among tIPD and PM in individuals aged <5 years and ≥5 years, and compared these rates between the 2005–2008 pre-PCV introduction period and two time points after PCV introduction, 2012 and 2016. Results: We enrolled 45, 853 tIPD cases; 17, 251 (38%) were PM. By 2016, IPD caused by all serotypes decreased 55% (95%CI −57% to −53%) for tIPD, and 54% for PM (95%CI −58% to −51%), 0.7% difference between estimates (p = 0.7). No significant differences were observed between PCV7-serotype disease reduction in tIPD and PM in both age groups or the additional 6 serotypes included in PCV13 in <5 year olds in 2012 and 2016. In 2012 there was a significant difference between increases in non-PCV13 serotype disease in those ≥5 years for tIPD and PM (32% greater increase in PM, p < 0.001), but this difference was absent by 2016. There was a significant difference between the estimated decrease in additional PCV13 type disease in 2016 between tIPD and PM for those aged ≥5 years (28% greater reduction in PM, p = 0.008). Conclusion: PM showed similar reductions to tIPD seven years after PCV introduction in vaccine serotype disease in those <5 years, and increases in non-vaccine serotype disease in all ages.